From Challenges to Opportunities: AI in English Language Teaching Classrooms - Basaula, Asmita (Kalika Journal of Multidisciplinary Studies, 2025)
Artificial Intelligence (AI) has become an increasingly influential force in education, reshaping traditional pedagogical approaches and offering new opportunities for learner autonomy, personalization, and engagement. In the context of English Language Teaching (ELT) in Nepal, however, questions remain about how teachers and students perceive AI’s role, benefits, and challenges. This study aims to explore these perceptions, focusing on the pedagogical affordances, ethical complexities, and technological barriers associated with AI integration in secondary-level classrooms. Employing a phenomenological qualitative design, the study collected data from five teachers and three students through semi-structured interviews. Data were analyzed thematically using Braun and Clarke’s six-phase framework, supported by ATLAS.ti9 software to ensure systematic coding and transparency. The analysis revealed three overarching themes: AI as a facilitator of student-centered pedagogy, systematic and echnological barriers such as limited access and linguistic bias, and ethical concerns including academic dishonesty, privacy, and overreliance. Collectively, the findings demonstrate that while AI can act as a supportive pedagogical ally, its effectiveness is shaped by contextual realities, ethical considerations, and user readiness. The study offers new empirical insights by capturing the lived experiences of Nepali ELT teachers and students, a context that has received little attention in global AI-ineducation research. These findings carry practical implications for strengthening educationalpolicy, designing teacher training that integrates ethical and pedagogical use of AI, and developing AI tools that are culturally and linguistically inclusive.